### Advertisement

### Advertisement

Last updated at Sept. 7, 2021 by Teachoo

Transcript

Ex 13.2, 2 Simplify and express each of the following in exponential form: (i) (2^3× 3^4 × 4)/(3 × 32) (2^3× 3^4 × 4)/(3 × 32) = (2^3× 4)/32 × 3^4/3 = (2^3 × 1)/8 × 3^4/3^1 = 2^3/8 × 34−1 = 2^3/8 × 33 ("As " 𝑎^𝑚/𝑎^𝑛 " = am−n" ) = 8/8 × 33 = 1 × 33 = 33

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.